Tubo-ovarian abscess. Prevalence in four decades at Hospital Nacional Arzobispo Loayza - Siu Au, Alejandro (2014)
Background: Tubo-ovarian abscess (TOA) is the response of female genitalia to focus infection; the abscess capsule allows perpetuation of the infection by isolation of germs and reduces antibiotics performance, becoming necessary surgical intervention as part of the problem solution. TOA is sequel of septic abortion, pelvic inflammatory disease (PID), and less frequently due to puerperal infection. Abscess rupture can be mortal. Objectives: To determine variation of tubo-ovarian abscess prevalence at a Peruvian national hospital since 1970 through 2010. Design: Retrospective study. Setting: Hospital Arzobispo Loayza, Lima, Peru. Participants: Women with tubo-ovarian abscess. Interventions: Review of clinical charts of patients with tubo-ovarian abscess and determination of the cause and variation throughout time. Main outcome measures: Prevalence and causes of tuboovarian abscess during four decades. Results: TOA decreased over the time studied with inversion of its main cause; in the early stage of this study the major cause was septic abortion (SA), whereas in recent years PID became the major cause. Conclusions: During the four decades studied tubo-ovarian abscess frequency decreased and the main cause septic abortion was displace by pelvic inflammatory disease.